Studi Empiris terhadap Efektivitas PenerapanKriteria Sewaguna Kapital yang Diunjukkan oleh PSAK No. 30: "Akuntansi Sewaguna Usaha" - Irfan Nursasmito; Sumiyana Sumiyana (The Indonesian Journal of Accounting Research, 2013)
This research investigates three criteria presented by PSAK (Indonesia's Financial Accounting Standard) No. 30. The criteria should support lessee to capitalize the lease transaction. However, the criteria in this standard are not applicable due to defect or unuseful criteria in comparison with SFAS No. 13. This research uses binary logistic regression to detect the probability in recognizing capital lease for lessee. This research concludes that two out of three criteria are not associated with the probability of capital lease recognition. This research also suggests that the requirement of this standard to fulfill fully to all criteria is not valid and logic. Finally, this research recommends that this standard has to be revised in order this standard has an ability to maintain its relevance and reliability.